2015
DOI: 10.1002/hed.24168
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hearing outcomes after treatment for early‐stage external auditory canal cancer

Abstract: Adequate techniques for reconstruction of the external auditory canal in combination with tympanoplasty after complete surgical resection is useful for hearing preservation in addition to good survival outcomes. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1110-E1116, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The hearing level in case 1, with hearing preservation, remained comparable to the healthy side. In irradiated cases, Morita et al 10 reported that hearing worsens after irradiation, but because case 1 did not receive irradiation, its impact on hearing could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The hearing level in case 1, with hearing preservation, remained comparable to the healthy side. In irradiated cases, Morita et al 10 reported that hearing worsens after irradiation, but because case 1 did not receive irradiation, its impact on hearing could not be determined.…”
Section: Discussionmentioning
confidence: 99%